ANALISIS HUKUM, EKONOMI, SOSIO-LEGAL PADA PENYELESAIAN PERKARA KEPAILITAN DAN PKPU DI PENGADILAN NIAGA - Muhammad Sulthan Nurraihan; Annisa Risqi Handayani; Ismawati Septiningsih (Sebelas Maret University, 2026)
The Indonesian Commercial Court plays a central role in resolving bankruptcy and debt restructuring disputes that have a significant impact on the survival of companies, industries, and the national economy, especially in the context of the protracted global economic crisis. This study aims to evaluate the effectiveness of the Indonesian Commercial Court in carrying out its duties, taking into account the legal, economic and social dimensions surrounding it. The research adopts a mixed-methods approach, with an analysis of 200 Commercial Court decisions, interviews with 25 commercial judges and 30 receivers, and a comparative analysis with the bankruptcy systems of developed countries, such as Singapore and Germany. The study found that although Indonesia's Bankruptcy Law is quite comprehensive, there is an imbalance between legal and economic interests in decision-making. One of the main weaknesses lies in the limited institutional capacity, lack of integration of economic considerations in decision-making, as well as the absence of an effective post-decision monitoring system of the Court. This study recommends deep reforms in Indonesia's insolvency system, which not only emphasize legal efficiency, but also support business sustainability through policies that are more adaptive to global market dynamics.